Yrast States and B(E2) Values of Even 100-102Ru Isotopes Using Interacting Boson Model (IBM-1) - Imam Hossain (Science Faculty of Chiang Mai University, 2019)
The yrast-state bands and E2 transition rates for the even 100-102Ru isotopes are studied in the framework of the interacting boson model (IBM-1). The values of the parameters have been determined using the IBM-1 Hamiltonian which yield the best fit to the available experimental energy levels. The theoretical energy levels have been obtained by Matlap computer program for Ruthenium isotopes with neutron number N= 56 and 58 up to spin-parity 28+ and 16+, respectively. Furthermore, the B(E2) values are calculated and compared with the experimental data. The ratio of excitation energies of the first 4+ and the first 2+ excitated states, R4/2, is also studied for the classification of symmetry of these nuclei. The moment of inertia and the potential energy surface of 100-102Ru isotopes also calculated. Back bending phenomena of those nuclei are studied. The calculated results of yrast energy band and B(E2) values are compared with the previous experimental results and the obtained theoretical calculations in IBM-1 are in good agreement with the experimental energy level. The results show that the 100-102Ru isotopes are vibrational deformed nuclei and they are dynamical symmetry U(5) in the interacting boson model IBM-1.